Optimal Paths on Urban Networks Using Travelling Times Prevision - Alfredo Cutolo; Carmine De Nicola; Rosanna Manzo; Luigi Rarità (Modelling and Simulation in Engineering)
We deal with an algorithm that, once origin and destination are fixed, individuates the route that permits to reach the destination in the shortest time, respecting an assigned maximal travel time, and with risks measure below a given threshold. A fluid dynamic model for road networks, according to initial car densities on roads and traffic coefficients at junctions, forecasts the future traffic evolution, giving dynamical weights to a constrained 𝐾 shortest path algorithm. Simulations are performed on a case study to test the efficiency of the proposed procedure.